Experimental Study on Influence of Microexpansive Concrete Self-Stress on Performance of Steel Pipe Concrete - Xin Liu; Yu-Zhou Zheng; Qin Fang; Heng-Bo Xiang; Hai-Chun Yan (Shock and Vibration)
To explore the influence of microexpansive concrete self-stress on the performance of steel pipe concrete, the expansion rate test of microexpansive concrete confined by steel tube was carried out with different expansion rates. Then, the mechanical properties of high-strength steel tube-confined microexpansive concrete (HSTCMC) short columns were conducted by the uniaxial compression test. The length-to-diameter ratio, the expansion rate of the microexpansive concrete, and the steel tube thickness were investigated in the study. Furthermore, the ABAQUS software was employed to analyze the microexpansive mechanism of the concrete, and it was verified by the uniaxial compression test. The test results show that the concrete possesses a remarkable volume expansion phenomenon, which was up to 150 με after four days of maintenance time. The mechanical properties of the HSTCMC short columns were greatly improved compared to the control RC pier. The yield and ultimate strength of the HSTCMC short columns can be enhanced to 8.9% and 14.6%, and with the content of expansive agent that increased from 8% to 12%. The finite element analysis results highlighted that the end constraint at the two ends has the biggest influence on the mechanical performance of the HSTCMC short columns, followed by the thickness of the steel tube and the content of the expansive agent. It should be noted that the self-stress of microexpansive concrete will be decreased with the increase in the length-to-diameter ratio, when the length-to-diameter ratio is less than four. Furthermore, the constraint effect of the circular steel tube on the microexpansive concrete is better than that of the rectangular section steel tube.